CNVs leading to fusion transcripts in individuals with autism spectrum disorder - Holt, R; Sykes, N; Conceição, I; Cazier, J; Anney, R; Oliveira, G; Gallagher, L; Vicente, A; Monaco, A; Pagnamenta, A (2012)
There is strong evidence that rare copy number variants (CNVs) have a role in susceptibility to autism spectrum disorders (ASDs). Much research has focused on how CNVs mediate a phenotypic effect by altering gene expression levels. We investigated an alternative mechanism whereby CNVs combine the 5′ and 3′ ends of two genes, creating a fusion gene. Any resulting mRNA with an open reading frame could potentially alter the phenotype via a gain-of-function mechanism. We examined 2382 and 3096 rare CNVs from 996 individuals with ASD and 1287 controls, respectively, for potential to generate fusion transcripts. There was no increased burden in individuals with ASD; 122/996 cases harbored at least one rare CNV of this type, compared with 179/1287 controls (P<0.89). There was also no difference in the overall frequency distribution between cases and controls. We examined specific examples of such CNVs nominated by case-control analysis and a candidate approach. Accordingly, a duplication involving REEP1-POLR1A (found in 3/996 cases and 0/1287 controls) and a single occurrence CNV involving KIAA0319-TDP2 were tested. However, no fusion transcripts were detected by RT-PCR. Analysis of additional samples based on cell line availability resulted in validation of a MAPKAPK5-ACAD10 fusion transcript in two probands. However, this variant was present in controls at a similar rate and is unlikely to influence ASD susceptibility. In summary, although we find no evidence that fusion-gene generating CNVs lead to ASD susceptibility, discovery of a MAPKAPK5-ACAD10 transcript with an estimated frequency of 1/200 suggests that gain-of-function mechanisms should be considered in future CNVs studies. © 2012 Macmillan Publishers Limited. All rights reserved.